Study and Communication Skills for College Freshmen - Ornos, Petra S.; Esgra, Cerila B. ; Gomez, Nieva G. ;| Verde, Stanley P. (Makati City, Philippines, 2006)
This book is primarily designed for first year college students taking up English 1. This was written in accordance to the ultimate goal of language learning, and the ability to use the language in purposeful communication.
Keywords: English language- study and teaching